Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1111/j.1349-7006.1992.tb01963.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency of Rearrangements of the ret and trk Proto‐oncogenes in Japanese Thyroid Papillary Carcinomas

Abstract: We investigated the frequency of rearrangements of the ret and trk proto‐oncogenes in Japanese thyroid tumors. DNAs from 38 thyroid papillary carcinomas and 14 follicular adenomas were analyzed by Southern blotting. Rearrangements of the ret and trk proto‐oncogenes were detected in one and two papillary carcinomas, respectively, but not in follicular adenomas. Analysis by a reverse transcriptase‐polymerase chain reaction method showed that the ret rearrangement‐positive tumor contained the PTC/refTPCchimeric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 10 publications
4
43
0
1
Order By: Relevance
“…However, the chimeric transcript of RET/PTC oncogene, has also been found in one study in follicular adenomas . Contrasting with the high and very similar frequency (about 60%) of activation observed in the Chernobyl tumors Ito et al, 1994;Klugbauer et al, 1995), the frequency of ret activation in`spontaneous' thyroid tumors varies widely between di erent studies: from 2.5% to 34% Delvincourt et al, 1996;SaõÈ d et al, 1994;Santoro et al, 1992;Wajjwalku et al, 1992;Zou et al, 1994). It has been postulated that this variation could be the result of the di erent geographical origins of populations studied, the age at tumor occurrence, or the sensitivity of the experimental methods used to detect the rearrangement.…”
Section: Introductionmentioning
confidence: 90%
“…However, the chimeric transcript of RET/PTC oncogene, has also been found in one study in follicular adenomas . Contrasting with the high and very similar frequency (about 60%) of activation observed in the Chernobyl tumors Ito et al, 1994;Klugbauer et al, 1995), the frequency of ret activation in`spontaneous' thyroid tumors varies widely between di erent studies: from 2.5% to 34% Delvincourt et al, 1996;SaõÈ d et al, 1994;Santoro et al, 1992;Wajjwalku et al, 1992;Zou et al, 1994). It has been postulated that this variation could be the result of the di erent geographical origins of populations studied, the age at tumor occurrence, or the sensitivity of the experimental methods used to detect the rearrangement.…”
Section: Introductionmentioning
confidence: 90%
“…These phenomena have seldom been detected in papillary thyroid carcinomas (less than 3%) in Japan, although until now Japanese investigators have examined this type of carcinoma only for the ret/PTC1 chimeric gene (Namba et al 1991;Wajjwalku et al 1992). The discrepancy in the reported frequency of ret/PTC oncogenes could be due to environmental, racial, or methodological factors.…”
Section: Introductionmentioning
confidence: 91%
“…The ret/ PTC1 oncogene is generally the most frequent form of RET rearrangement found in Caucasian populations, although the precise frequency varies with different studies (Jhiang et al 1992;Santoro et al 1992;Williams et al 1996;Bounacer et al 1997). In Japan, Namba et al (1991) examined ten papillary thyroid carcinomas only for ret/PTC1 rearrangements and found no rearrangement; Ishizaka et al (1991) found one ret/PTC1 rearrangement among 11 carcinomas, and Wajjwalku et al (1992) found only one such alteration among 38 carcinomas. On the basis of those observations, RET gene rearrangements in papillary thyroid carcinomas were thought to be rare in the Japanese population.…”
Section: Short Horizontal Bars Represent Hybridization Probes (Probesmentioning
confidence: 99%
“…The most common techniques include Southern blotting, direct gel visualization of the RT-PCR amplicons and hybridization of blotted RT-PCR products. Meta-analysis of the data published worldwide over a greater than 10-year period (Table 3) demonstrates an average prevalence of 18% for Southern blotting (67/370 cases tested, range 0-33%), [26][27][28][29][30][31] 15% for direct visualization of the RT-PCR amplicons (47/309 cases tested, range 4-45%) 7,32-35 and 48% for hybridization of blotted RT-PCR products (153/314 cases tested, range 0-85%). 4,[21][22][23][36][37][38][39] Allowing for the fact that Southern blotting permits the identification of all RET/PTC variants while the cases analyzed by RT-PCR listed above only screened the tumors for RET/PTC1, -2 and -3, there is a good correspondence between the sensitivity of Southern blotting and of direct gel visualization of RT-PCR products, as also demonstrated by parallel analysis of the same samples with the two methods.…”
Section: Discussionmentioning
confidence: 99%